Cerrado deforestation threatens regional climate and water availability for agriculture and ecosystems - Rodrigues, Ariane A.; Macedo, Marcia N.; Silvério, Divino V.; Maracahipes, Leandro; Coe, Michael T.; Brando, Paulo M.; Shimbo, Julia Z.; Rajão, Raoni; Soares‐Filho, Britaldo; Bustamante, Mercedes M. C. (Global change biology, 2022)
The Brazilian Cerrado is one of the most biodiverse savannas in the world, yet 46% of its original cover has been cleared to make way for crops and pastures. These extensive land‐use transitions (LUTs) are expected to influence regional climate by reducing evapotranspiration (ET), increasing land surface temperature (LST), and ultimately reducing precipitation. Here, we quantify the impacts of LUTs on ET and LST in the Cerrado by combining MODIS satellite data with annual land use and land cover maps from 2006 to 2019. We performed regression analyses to quantify the effects of six common LUTs on ET and LST across the entire gradient of Cerrado landscapes. Results indicate that clearing forests for cropland or pasture increased average LST by ~3.5°C and reduced mean annual ET by 44% and 39%, respectively. Transitions from woody savannas to cropland or pasture increased average LST by 1.9°C and reduced mean annual ET by 27% and 21%, respectively. Converting native grasslands to cropland or pasture increased average LST by 0.9 and 0.6°C, respectively. Conversely, grassland‐to‐pasture transitions increased mean annual ET by 15%. To date, land changes have caused a 10% reduction in water recycled to the atmosphere annually and a 0.9°C increase in average LST across the biome, compared to the historic baseline under native vegetation. Global climate changes from increased atmospheric greenhouse gas concentrations will only exacerbate these effects. Considering potential future scenarios, we found that abandoning deforestation control policies or allowing legal deforestation to continue (at least 28.4 Mha) would further reduce yearly ET (by −9% and −3%, respectively) and increase average LST (by +0.7 and +0.3°C, respectively) by 2050. In contrast, policies encouraging zero deforestation and restoration of the 5.2 Mha of illegally deforested areas would partially offset the warming and drying impacts of land‐use change. Resumo O Cerrado brasileiro é uma das savanas mais biodiversas do mundo. Apesar disso, 46% da sua cobertura original foi desmatada para dar lugar a cultivos agrícolas e pastos. Estas extensas transições de uso do solo (LUT) têm o potencial de influenciar o clima regional, reduzindo a evapotranspiração (ET), aumentando a temperatura da superfície terrestre (LST) e por fim reduzindo a precipitação. O objetivo deste estudo foi quantificar os impactos de LUTs sobre ET e LST no Cerrado, combinando dados do satélite MODIS com mapas anuais de uso e cobertura do solo de 2006–2019. Foram realizadas análises de regressão para quantificar os efeitos de seis LUTs usuais sobre ET e LST, ao longo de todo o gradiente de paisagens do Cerrado. Os resultados indicaram que a retirada de florestas para dar lugar à agricultura ou pastagem aumentou a LST média em ~3.5°C e reduziu a ET média anual em 44% e 39%, respectivamente. Transições de formações savânicas para agricultura ou pastagem aumentaram a LST média em 1.9°C e reduziram a ET média anual em 27% e 21%, respectivamente. A conversão de campos nativos para agricultura ou pastagem aumentou a LST média em 0.9 e 0.6°C, respectivamente. Em contrapartida, transições de formações campestres nativas para pastagens aumentaram a ET média anual em 15%. Até o momento, as mudanças de uso do solo causaram redução de 10% da água reciclada para a atmosfera anualmente e aumento de 0.9°C da LST média ao longo do bioma, em comparação com a linha de base histórica sob vegetação nativa. As mudanças climáticas globais decorrentes do aumento das concentrações atmosféricas de gases do efeito estufa irão exacerbar esses efeitos. Considerando potenciais cenários futuros, observou‐se que o abandono das políticas de controle do desmatamento ou o avanço do desmatamento legal (ao menos 28.4 Mha) reduziriam a ET anual (em −9% e −3%, respectivamente) e aumentariam a LST média (em +0.7 e +0.3ºC, respectivamente) até 2050. Por outro lado, políticas que promovam desmatamento zero e restauração dos 5.2 Mha de áreas ilegalmente desmatadas compensariam parte dos impactos de aquecimento e seca causados por alterações de uso do solo. Researchers have long studied the role of tropical forests in regulating climate. This study shows that grasslands and savannas are also critical for regulating heat and moisture exchange. We address the historic and projected impacts of agricultural expansion on regional climate in the Brazilian Cerrado, one of the most biodiverse savannas in the world. Large‐scale conversion of forests and savannas to agricultural land uses has caused significant warming and drying in a region already facing water scarcity. Grassland conversion has also contributed to increased surface temperatures. Recent weakening of environmental policies could further threaten the region's climatic stability.